Situation Report: Hungary, 26 October 1979 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Light Metal - Heavy Problems: The Hungarian Aluminum Industry The Cost of Health Tourism Cum Hunting - A Useful Source of Hard Currency I Entrust Myself to God: A Conversation with Religious Youth Media Coverage of the Pope's Visit to Ireland and the US New Producer Prices in Agriculture